Nigerian Youths and Popular Music: The Media Literacy Imperative - Layefa, Goodluck; Ezenagu, Ngozi; Johnson, William A.; Adedara, Marcus (Àgídìgbo: ABUAD Journal of the Humanities, 2016)
The pervasiveness of popular music and its attendant influence on contemporary youths in the Nigerian society has attracted the attention of government, parents and researchers. Beyond measures proffer to curb the negative influence of popular music on youths, the youths themselves need to understand the principles and practices of the mass media. Against this backdrop, the study while employing contextual approach and relying largely on secondary data, examines the Nigerian youths and popular music via the media literacy imperative. The paper posits that to ameliorate the negative effects of popular music on Nigerian youths, the youth themselves must have deep understanding of the power of media technology; knowledge about the producers of media contents; and the ability to thoroughly examine media contents (audio visual images), as against the background of the expected role the mass media are to perform in societies. The paper recommends among others the inclusion of media literacy studies in the curriculum of both secondary and tertiary institutions; government linking up with other developed countries to explore the possibility of shutting off the underage from listening! viewing damaging media/musical contents; the interplay of which may probably help to avert a possible dreadful future realities of youths with perverted behaviours (through damaging media/musical content) in the Nigerian society.